THE ROAD LESS TAKEN: DIFFERENTIATED INSTRUCTION (DI) AS PRACTICED BY GRADE 7 MATHEMATICS TEACHERS IN THE PHILIPPINES - Magayon, Ma Victoria C; Tan, Emily B (PUPIL: International Journal of Teaching, Education and Learning, 2020)
In the K-12 curriculum program applied globally, teachers are challenged to apply the Differentiated Instruction (DI) which is responsive to the needs of all students and facilitates learning. In the Philippines, the Department of Education recently mandated the implementation of DI in the K-12 curriculum. Hence, this study sought to answer research question: What differentiations are practiced by the Grade 7 Mathematics teachers in their classes? Data gathered from lesson plans, interviews, and classroom observations of 21 Grade 7 Filipino mathematics teachers were qualitative analyzed through the Framework Analysis by Ritchie and Lewis (2013). Findings show that Maker’s principles of differentiation on content, process, and product were applied in instruction though not to the fullest; and Tomlinson’s principles are embedded in the teaching strategies and student’s activities, considering student’s readiness and interests. Instruction is modified to enhance engagement in learning mathematics; activities are selected to ensure that students are able to connect, scaffold, develop mastery of the lesson, and unleash creativity; and performance tasks and evaluations are based on the preference of the students. Though there are various evidence of the application of the principles of DI by the Filipino mathematics teachers, the extent of its implementation in various disciplines can be explored qualitatively and quantitatively.